Putusan Verstek Dalam Badan Penyelesaian Sengketa Konsumen (BPSK) Kabupaten Purbalingga Dalam Menangani Sengketa Konsumen (Studi Kasus Putusan Nomor 02/BPSK-PBG/PUT-Arbitrase/VII/2016) - Bagus, Andika; Wardhani, Susilo (UMPurwokerto Law Review, 2024)
Abstract The rapid progress of science, communication technology and infotmatika today has supported the expansion of the space for trade in goods and services which has helped increase the development of the economic sector. The research method used in this research is normative juridical, with secondary legal data, the secondary data includes 3 (Three) types, namely primary legal materials, secondary legal materials, and tertiary legal materials and then accompanied by identification and clarification of legal facts as additional data. This research aims, First, to know and analyze the legal force of the decision of the Consumer Dispute Resolution Agency (BPSK) through the Consumer Dispute Resolution Agency (BPSK) in Purbalingga. Second, to find out the obstacles faced by the parties in dispute resolution at the Consumer Dispute Resolution Agency in resolving consumer disputes. BPSK decisions that are final, and binding based on the results of conciliation, arbitration, and mediation, have a final meaning meaning that the dispute resolution is over and finished, while the meaning of binding means that it applies forcefully and must be carried out by the parties. BPSK decisions from the results of conciliation, arbitration, and mediation are final and binding and only apply within the scope of settlement at BPSK. Keywords: Consumer, Dispute Abstract Pesatnya kemajuan ilmu pengetahuan, teknologi komunikasi dan infotmatika saat ini telah mendukung perluasan ruang gerak perdagangan barang dan jasa yang ikut meningkatan perkembangan bidang perekonomian. Metode penelitian yang digunakan dalam penelitian ini adalah yuridis normatif, dengan data hukum sekunder, data sekunder tersebut mencakup 3 (Tiga) jenis yaitu bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier lalu disertai dengan identifikasi dan klarifikasi fakta hukum sebagai data tambahan. Pada penelitian ini bertujuan, Pertama untuk mengetahui dan menganalisis kekuatan hukum putusan Badan Penyelesaian Sengketa Konsumen (BPSK) melalui Badan Penyelesaian Sengketa Konsumen (BPSK) di Purbalingga. Kedua, untuk mengetahui kendala yang dihadapi para pihak dalam penyelesaian sengketa di Badan Penyelesaian Konsumen dalam penyelesaian sengketa konsumen. Putusan BPSK yang bersifat final dan mengikat berdasarkan hasil konsiliasi, arbitrase, dan mediasi, memiliki makna final berarti penyelesaian sengketa sudah berakhir dan selesai, sedangkan makna mengikat berarti berlaku memaksa dan harus dijalankan para pihak. Putusan BPSK dari hasil konsiliasi, arbitrase, dan mediasi bersifat final dan mengikat hanya berlaku dalam lingkup penyelesaian di BPSK. Keywords: Konsumen, Sengketa